Trickling out effects of abusive supervision: A social information processing perspective. - Tariq, Hussain; Khan, Abdul Karim; Hochwarter, Wayne A; Muchiri, Michael; Babalola, Mayowa T (Human Relations, 2026)
Can an employee rationalize their supervisory abuse to the point where sabotaging customers seems justified? Drawing from the social information processing theory perspective, we introduce three distinct types of supervisor–supervisee dyadic cognitive influences (i.e. attention-shifting, role-sending, and role-modeling mechanisms) to explain the trickle-out effects of abusive supervision on customers. We hypothesized that an abused employee's perception of acceptability of norm violations, role ambiguity, and role-modeling influence mediates the effects of abusive supervision on customer-directed sabotage. Furthermore, we developed a process-moderated mediation model to explain how different levels of psychological and physical proximity shape these effects. Across two studies in distinct face-to-face service contexts, we found that the perceived acceptability of norm violations (Study 2), role ambiguity (Study 1 and Study 2), and role-modeling influence (Study 1 and Study 2) trickle out the effects of abusive supervision on customers. Interestingly, these trickle-out effects via role ambiguity and role-modeling influence are intensified when employees are psychologically close to their supervisor but physically distant from customers, but under these moderation mediation conditions, the trickle-out effect via perceived acceptability of norm violations has been weakened. Our findings offer new insights into how abusive behaviors ripple through service organizations, affecting not just internal dynamics but external customer relations as well.